Air Pollution and Oral Health: An Overall Insight From Genetic Causality - Ziyang Zheng; Mingzhang Xu; Yifei Wang; Lan Wang; Yang Zhou; Yunyi Deng; Ke Yu (International Dental Journal)
Background: A growing body of epidemiological data consistently links air pollution to various adverse health outcomes. However, the potential connection between air pollution and the risk of oral diseases remains underexplored. Methods: This study utilized a two-sample Mendelian randomization approach to assess the causal relationship between air pollution and oral diseases. Six categories of air pollution were considered as exposures: nitrogen oxides (NOx), nitrogen dioxide (NO2), particulate matter (PM2.5, PM2.5-10, PM10), and PM2.5 absorbance. The outcomes included 18 oral health-related diseases drawn from the Finngen R10 dataset, the Gene-Lifestyle Interactions in Dental Endpoints consortium, and the Oncoarray oral cavity and oropharyngeal cancer consortium. Sensitivity analyses were performed to validate the primary inverse-variance weighted estimates using methods such as weighted median, weighted mode, and MR Egger. Results: The inverse-variance weighted analysis demonstrated a detrimental effect of air pollution on multiple oral health conditions, yielding 5 positive associations including PM2.5 with oral leukoplakia, gingivitis and periodontitis; PM2.5-10 with pulp and periapical diseases, and NO2 with gingivitis and periodontitis, and oral cavity, salivary glands and jaws diseases. Sensitivity tests showed no evidence of heterogeneity or pleiotropy, affirming the robustness of the findings. Conclusion: This study highlights the detrimental impact of air pollution on oral health, emphasizing the need for further research into the underlying mechanisms and interactions. These findings reinforce the importance of implementing environmental interventions to mitigate the associated risks for oral health.